A randomized controlled pilot trial of a smoking cessation intervention for US women living with HIV: telephone-based video call vs voice call - Kim SS; Darwish S; Lee SA; Sprague C; DeMarco RF (Dove Medical Press, 2018)
Sun S Kim,1 Sabreen Darwish,1 Sang A Lee,1 Courtenay Sprague,1–3 Rosanna F DeMarco1 1Department of Nursing, College of Nursing and Health Sciences, University of Massachusetts Boston, Boston, MA, USA; 2Department of Conflict Resolution, Global Governance and Human Security, John W. McCormack Graduate School of Policy and Global Studies, Boston, MA, USA; 3Wits Reproductive Health and HIV Institute, School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa Background: People living with HIV smoke at a rate three times that of the general population. This randomized controlled pilot trial tested the feasibility and acceptability of a video-call smoking cessation intervention in women living with HIV and its preliminary efficacy compared with a voice-call smoking cessation intervention. The study focused on women due to a paucity of studies among this population, and women are less likely than men to quit smoking when provided with conventional treatment. Methods: Participants in both arms received an HIV-tailored smoking cessation intervention comprising eight 30-minute weekly counseling sessions in conjunction with active nicotine patches for 8 weeks. The only difference between the two arms was the delivery mode of the intervention: via either telephone-based video or voice call. Survival analysis and a Cox proportional hazard regression model were performed to identify factors predicting 6-month prolonged abstinence from smoking. Results: A video-call intervention was almost 30% less feasible than a voice-call intervention because women in their 50s and 60s or poorer women living in some southern states did not have access to video-call equipment. However, those who received the video-call intervention were more likely to complete the study than those who had the voice-call intervention. There was no difference in the acceptability of the two interventions. A survival analysis revealed that those in the video arm were significantly more likely to maintain smoking abstinence over the 6-month follow-up period than those in the voice arm (log rank χ2=4.02, P<0.05). Conclusion: Although a video-call intervention is less feasible than a voice-call intervention, the former seems to outperform the latter in achieving long-term smoking abstinence for women living with HIV, which may offer an advantage over establishing therapeutic alliance and visually monitoring their adherence to nicotine patches. Clinical trial registration: ClinicalTrials.gov NCT02898597. Keywords: HIV, women, smoking cessation intervention, video call